Solvability and asymptotic behavior of a population problem taking into account random mating and females' pregnancy - Skakauskas, Vladas (Zielona Góra: Uniwersytet Zielonogórski)
Two deterministic age-sex-structured population dynamics models are discussed taking into account random mating of sexes (without formation of permanent male-female couples), possible destruction of the fetus (abortion), and female's pregnancy.
Keywords: population dynamics; random mating; gestation of females; migration